A review of digital fashion research: before and beyond communication and marketing. Issue 3 (2nd September 2021) - Nobile, Tekila Harley; Noris, Alice; Kalbaska, Nadzeya; Cantoni, Lorenzo
ABSTRACT: This paper focuses on the field of digital fashion and its development by providing an overview regarding fashion design and culture. It is part of a larger research that involved a literature review of 491 relevant papers. From the analysis of this corpus, three main categories were identified: Communication and Marketing, Design and Production and Culture and Society. This study focuses on the categories Design and Production and Culture and Society, which collectively gathered indicatively 48% of the selected literature. It presents its relevant studies and sub-categories, providing a rich and varied map of them and contributing to better design in further research in digital fashion.